Importance of bacterial endotoxin (LPS) in endodontics A importância da endotoxina bacteriana (LPS) na endodontia atual - Mario Roberto Leonardo; Raquel Assed Bezerra da Silva; Sada Assed; Paulo Nelson-Filho (University of São Paulo, 2004)
New knowledge of the structure and biological activity of endotoxins (LPS) has revolutionized concepts concerning their mechanisms of action and forms of inactivation. Since the 1980's, technological advances in microbiological culture and identification have shown that anaerobic microorganisms, especially Gram-negative, predominate in root canals of teeth with pulp necrosis and radiographically visible chronic periapical lesions. Gram-negative bacteria not only have different factors of virulence and generate sub-products that are toxic to apical and periapical tissues, as also contain endotoxin (LPS) on their cell wall. This is especially important because endotoxin is released during multiplication or bacterial death, causing a series of biological effects that lead to an inflammatory reaction and resorption of mineralized tissues. Thus, due to the role of endotoxin in the pathogenesis of periapical lesions, we reviewed the literature concerning the biological activity of endotoxin and the relevance of its inactivation during treatment of teeth with pulp necrosis and chronic periapical lesion. O conhecimento mais aprofundado sobre a estrutura e atividade biológica das endotoxinas (LPS) revolucionou os conceitos sobre seu mecanismo de ação e formas de inativação. A partir da década de 80, os avanços tecnológicos na cultura e identificação microbiológica demonstraram que, em canais radiculares de dentes portadores de necrose pulpar e lesão periapical crônica, visível radiograficamente, predominam microrganismos anaeróbios, particularmente os gram-negativos. Como se sabe, os microrganismos gram-negativos, além de possuírem diferentes fatores de virulência e gerarem produtos e sub-produtos tóxicos aos tecidos apicais e periapicais, contêm endotoxina em sua parede celular. Esse conhecimento é particularmente importante, uma vez que a endotoxina é liberada durante a multiplicação ou morte bacteriana, exercendo uma série de efeitos biológicos relevantes, que conduzem a uma reação inflamatória e à reabsorção dos tecidos mineralizados. Tendo em vista o papel da endotoxina na patogênese das lesões periapicais, os autores realizaram uma revisão da literatura específica, abordando suas atividades biológicas e a importância de sua inativação durante o tratamento de dentes portadores de necrose pulpar e lesão periapical.